TCR β CDR3 repertoire remodeling in pediatric myocarditis reveals clonal expansion and disease-associated public clonotypes - Lin, Xixiong; Zhang, Xing; Zhang, Liping; Hui, Linhu; Su, Zhongjian; Liu, Xingzhu; Li, Bin; Li, Jun; Chen, Yanfei (Frontiers in Immunology, 2026)
BackgroundPediatric myocarditis is an inflammatory disease of the heart with heterogeneous clinical presentations and poorly understood immune mechanisms. T cell receptor (TCR) repertoire profiling provides insights into disease-associated adaptive immune responses.MethodsWe performed high-throughput sequencing of TCR β chain CDR3 repertoires from 28 peripheral blood samples of pediatric myocarditis patients (Myo) and nine age-matched healthy controls (NC). Clonal diversity, V and J gene usage, CDR3 length distribution, clonotype sharing, and antigen-specific annotations were systematically analyzed.ResultsThe Myo group exhibited significantly reduced clonal diversity as measured by D50 and Chao1 indices, accompanied by expansion of large clones and reduced representation of small clones. Distinct biases in V and J gene usage were observed, with increased TRBV14, TRBV28, TRBJ1-1, TRBJ1-2, TRBJ1-5, TRBJ1-6, and TRBJ2-2, and decreased TRBV9, TRBJ2-4, TRBJ2-5, and TRBJ2-7. CDR3 length distribution showed an enrichment of longer sequences in myocarditis patients, alongside altered nucleotide insertions/deletions and amino acid usage. Clonotype sharing was markedly higher in the Myo group, and 16,460 public clonotypes were detected in ≥10 patients. Database annotation revealed an enrichment of matches to pathogen-associated TCR records, predominantly associated to Mycobacterium tuberculosis, influenza, cytomegalovirus, and Epstein–Barr virus. Seventeen high-frequency clonotypes were highlighted as candidate myocarditis-related TCR signatures based on database matches.ConclusionsOur study demonstrates distinct repertoire remodeling in pediatric myocarditis, characterized by reduced diversity, skewed V/J gene usage, biased CDR3 composition, and enriched public clonotypes. These findings provide novel insights into disease-related adaptive immune responses and may inform biomarker discovery for diagnosis and therapeutic strategies.